Practice of Kangoo Jumps Fitness to improve female students' cardiorespiratory fitness - T.I. Mokrova; A. Yu. Osipov; M. D. Kudryavtsev; R. S. Nagovitsyn; K. K. Markov (Physical Education of Students, 2018)
Purpose : Experts record the deterioration of the physical and cardiorespiratory fitness of students. Scientists recommend using fitness training in the practice of teaching students to increase cardiorespiratory fitness. The purpose of the research is to increase the level of cardiorespiratory fitness of female students by practicing Kangoo Jumps fitness in the practice of physical education. Material : participants are female students (n = 53, age - 19-20 years old). The study period was 10 months. Some females (n = 17) used Kangoo Jumps fitness in the practice of physical education. Indicators of physical and cardiorespiratory fitness were evaluated by the following methods: step test, Functional fitness assessment tests. Statistical data analysis was performed applying the Mann - Whitney U - test. Results : The test results (step test) revealed a significant (P <0.05) advantage of females practicing Kangoo Jumps fitness. The results are approximately the same for all females in most of the functional fitness assessment tests. The lowest weight gain (about 0.8 kg) is shown by females who used Kangoo Jumps fitness. Body mass indexes (from 1.8 to 2 kg.) were increased by students who used other types of fitness. Conclusions : It was revealed the possibility of increasing the cardiorespiratory fitness level of female students practicing Kangoo Jumps fitness in the practice of physical education. It was found the ability to control the increase in body weight of females.